(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Exposure to extremely high radiation levels can cause severe health implications such as skin burns or acute radiation syndrome and long-term health consequences, including cancer and cardiovascular disease. Unfortunately, many patients are often unaware of the hazards associated with radiation exposure.Objective: To assess the current awareness of individuals attending the department of radiology regarding radiation exposure hazards and the effectiveness of the formal teaching program on radiation exposure hazards among them.Method: The study was carried out in 50 randomly selected individuals aged 30-50 years hospitalized in the radiology department of Krishna hospital, Karad. To obtain socio-demographic details and expert status, we used a questionnaire for pre-test and post-test. Descriptive and inferential statistics were performed through Instat software to analyze the obtained data.Result: Prior to the start of the training program, 60% of patients had no knowledge about the hazards related to radiation exposure.After attending the structured training program, the level of knowledge was good in 44% of patients, average in 48%, poor in 8% of patients. There was no significant association between the pre-test score of knowledge level and demographic variables, including age, occupation, and source of information. The significantly higher post-test score for knowledge level for hazards of radiation exposure was observed in patients as compared to the pre-test score.Conclusion: The structured teaching program could be an effective method to improve the knowledge level in patients regarding the hazards associated with radiation exposure.